Inhibition of Osteoblast Function by Brucella abortus is Reversed by Dehydroepiandrosterone and Involves ERK1/2 and Estrogen Receptor - Gentilini, María Virginia; Pesce Viglietti, Ayelén Ivana; Arriola Benitez, Paula Constanza; Iglesias Molli, Andrea Elena; Cerrone, Gloria Edith; Giambartolomei, Guillermo Hernán; Delpino, María Victoria (Frontiers in Immunology, 2018)
Brucella abortus induces an inflammatory response that stimulates the endocrine system resulting in the secretion of cortisol and dehydroepiandrosterone (DHEA). Osteoarticular brucellosis is the most common presentation of the active disease in humans and we have previously demonstrated that B. abortus infection inhibits osteoblast function. We aimed to evaluate the role of cortisol and DHEA on osteoblast during B. abortus infection. B. abortus infection induces apoptosis and inhibits osteoblast function. DHEA treatment reversed the effect of B. abortus infection on osteoblast by increasing their proliferation, inhibiting osteoblast apoptosis and reversing the inhibitory effect of B. abortus on osteoblast differentiation and function. In contrast, cortisol increased the effect of B. abortus infection. Cortisol regulates target genes by binding to the glucocorticoid receptor (GR). B. abortus infection inhibited GR-α expression. Cells responses to cortisol not only depend on GR expression but also on its intracellular bioavailability, that is dependent on the activity of the isoenzymes 11β-HSD (hydroxysteroid dehydrogenase type)-1, 11β-HSD2 (which convert cortisone to cortisol and viceversa, respectively). Alterations in the expression of these isoenzymes in bone cells are associated with bone loss. B. abortus infection increased 11β-HSD1 expression but had no effect on 11β-HSD2. DHEA reversed the inhibitory effect induced by B. abortus infection on osteoblast matrix deposition in an estrogen receptor (ER)- and ERK1/2-dependent manner. We conclude that DHEA intervention improve osteoblast function during B. abortus infection making it a potential candidate to ameliorate the osteoarticular symptoms of brucellosis.